In-Flight Identification of Magnetometer and Attitude Determination System for Land-survey Mini-satellite∗. Issue 11 (2015) - Somov, Yevgeny; Butyrin, Sergey; Hajiyev, Chingiz
Abstract: We present discrete algorithms for in-flight identification, calibration and alignment of a low cost strap-down inertial navigation system with correction by signals from the Sun and magnetic sensors. Proposed algorithms are simulated through attitude dynamics of a small land-survey satellite.